Magdalenska gora Družbena struktura in grobni rituali železnodobne skupnosti = Social structure and burial rites of the Iron Age community - Tecco Hvala, Sneža (Opera Instituti Archaeologici Sloveniae, 2012)
The finds and preserved grave groups from its tumulus cemeteries, which are kept in several museums in different countries (Narodni muzej Slovenije, Ljubljana~Naturhistorisches Museum, Wien~Peabody Museum of Harvard University in Cambridge, USA), give a good insight into the cultural and social processes of the time. Together with notes on the circumstances of find and contents of graves, they represent a valuable source for the study of social structure and differentiation, as well as cultural identity.